2010
DOI: 10.1245/s10434-010-1325-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors After Surgical Resection for Intrahepatic, Hilar, and Distal Cholangiocarcinoma

Abstract: R0 resection and adjuvant chemotherapy may be mandatory to achieve long-term survival for patients with cholangiocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
158
4
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(189 citation statements)
references
References 37 publications
16
158
4
11
Order By: Relevance
“…Previous studies of survival in CCA patients have focused on specific subgroups-such as those at advanced stage (Park et al, 2009), receiving surgical resection (Murakami et al, 2011;Pattanathien et al, 2013;Sriputtha et al, 2013) or adjuvant therapy (Knüppel et al, 2012), or specific tumour locations (Cheng et al, 2007;Hasegawa et al, 2007;Nakagohri et al, 2008;Guglielmi et al, 2009;Bunsiripaiboon et al, 2010;Cho et al, 2010;Nuzzo et al, 2010;Li et al, 2011). In addition, most studies were retrospective, only one prospective study (Mihalache et al, 2010) has been reported, and there are none from Asian countries.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of survival in CCA patients have focused on specific subgroups-such as those at advanced stage (Park et al, 2009), receiving surgical resection (Murakami et al, 2011;Pattanathien et al, 2013;Sriputtha et al, 2013) or adjuvant therapy (Knüppel et al, 2012), or specific tumour locations (Cheng et al, 2007;Hasegawa et al, 2007;Nakagohri et al, 2008;Guglielmi et al, 2009;Bunsiripaiboon et al, 2010;Cho et al, 2010;Nuzzo et al, 2010;Li et al, 2011). In addition, most studies were retrospective, only one prospective study (Mihalache et al, 2010) has been reported, and there are none from Asian countries.…”
Section: Introductionmentioning
confidence: 99%
“…99 Postoperative survival rate for DCC has been reported between 18%-54%. 101 Twenty-three percent 5-year survival rate and median survival of 18 months were reported in a series of 563 patients. 102 Surgical mortality in large published series has been less than 3%.…”
Section: Distal Cholangiocarcinomamentioning
confidence: 98%
“…The statistically significant favorable parameters were higher degree of differentiation, a more favorable primary tumor factor by TNM staging, absence of LN metastases and R0 surgical margins. 36 …”
Section: Distal Cholangiocarcinomamentioning
confidence: 99%